Quo Vadis Budgetary Slack? A Bibliometric Analysis from 1985 to 2023 - Neny Desriani; Aryan Danil Mirza. BR; Fania Anjani Suharjo; Widya Fatmawati; Rosa Hilya Robiah; Dewi Sukmasari (Proceeding International Conference on Accounting and Finance, 2024)
Budget is one of the important things in a company because budget can describe how a company runs its business. Therefore, the company makes every effort to make its budget look good, one of which is by making deviations. A popular budget deviation, namely Budgetary Slack. Research about Budgetary Slack has been done a lot since the past and continuing. For this reason, research using bibliometric methods related to Budgetary Slack needs to be done, with the hope of increasing readers’ knowledge and for the sustainability of Budgetary Slack research in the future. This research used bibliometric methods and used 72 scientific articles from 1985-2023 which came from the Scopus database. Frequency analysis was carried out using Microsoft Excel, then visualized using VOS Viewer, and Harzing’s Publish or Perish was used for the citation matrix. Thus, it is hoped that research using the bibliometric method will not only provide broader insight regarding the development of literature about Budgetary Slack but also provides a strong foundation for further research development on similar areas in the future.